LEGAL POLICY OF GIVING MEDICINE FOR HEALTHCARE INSURANCE RECIPIENTS IN JUSTICE-BASED HOSPITALS: Legal Policy, Giving Medicine, Justice-Based PBI. - Muhamad Rizki Syafaat (Omnibus Law Journal, 2021)
Legal policies that prioritize the values of justice will bring prosperity. In health services, the values of justice should also be applied, especially for those who are the healthcare insurance recipients. There is no longer any neglect service of providing medicines for patients, especially patients who receive healthcare insurance at the hospital, therefore it is necessary to apply more supervision to health workers. So that in the future all problems related to medicine delivery services for healthcare insurance recipients at hospitals can be carried out properly and without discrimination. When talking about legal policies in health services, the regulations that have been made should lead to how the community, especially the poor and the underprivileged, in this case, is the healthcare insurance recipients (PBI) must get services that are fair and without any discrimination. And to avoid losses that will have an impact on both parties, both the hospital as the provider of health services and the patient as the recipient of health services, so that there is no civil lawsuit.